KESIAPANKERJA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERIPADANG PADA ERA MASYARAKAT EKONOMI ASEAN (MEA) DITINJAU DARITINGKAT MOTIVASI & LATAR BELAKANG ORANGTUA - Fitra Hayati; Agus Irianto; Rani Sofya (Jurnal Ecogen, 2018)
Abstract:The number of Indonesian higher educated unemployment indicates students unpreparedness in entering the workforce.The purpose of this research is to find the influence of motivation and parent’s background to the readiness of collage student at economic faculty, Universitas Negeri Padang, in ASEAN economic community.The method of this research wasdescriptive  with quantitative approach. The population of this research were the students at Economic Faculty with 439 students. The sampel was 81 students by  using simple random sampling method. The data was collected by using questionnaire and analyzed by using binomial regression with SPSS. The result of this research has concluded (1) there is a influence of motivation, parents’s education, parents’s job and parents’s income to the students readiness for working; (2) there is a influenceof motivation to the students readiness for working; (3) there is no influence between parents’s education to the students readiness for working; (4) there is no influence between parent’s job to the the students readiness for working; (5) there is a influence parents’s income to the students readiness for working.Therefore, students have to improve their self motivation in order to have a good readiness in competing in the world of work, and also parents must attention the facilities needed by their children to support the potential.Keywords:Work Readiness, Motivation, Background Parents , ASEAN Economic Community